2020
DOI: 10.3390/ijms21093359
|View full text |Cite
|
Sign up to set email alerts
|

Swiprosin-1/EFhD-2 Expression in Cardiac Remodeling and Post-Infarct Repair: Effect of Ischemic Conditioning

Abstract: Swiprosin-1 (EFhD2) is a molecule that triggers structural adaptation of isolated adult rat cardiomyocytes to cell culture conditions by initiating a process known as cell spreading. This process mimics central aspects of cardiac remodeling, as it occurs subsequent to myocardial infarction. However, expression of swiprosin-1 in cardiac tissue and its regulation in vivo has not yet been addressed. The expression of swiprosin-1 was analyzed in mice, rat, and pig hearts undergoing myocardial infarction or ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Tu Y, et al found miR-34c-5p played a crucial role in cerebral IR injury via in ammatory and apoptotic signaling pathways [40,41]. According to reports, miR-34c-5p participates in cardiac remodeling and repair during post-ischemic heart injury [42]. Our research supplemented the above results.…”
Section: Discussionsupporting
confidence: 85%
“…Tu Y, et al found miR-34c-5p played a crucial role in cerebral IR injury via in ammatory and apoptotic signaling pathways [40,41]. According to reports, miR-34c-5p participates in cardiac remodeling and repair during post-ischemic heart injury [42]. Our research supplemented the above results.…”
Section: Discussionsupporting
confidence: 85%
“…[ 38 39 ] According to reports, miR-34c-5p participates in cardiac remodeling and repair during postischemic heart injury. [ 40 ] Our research supplemented the above results. In addition, we observed that HR condition increased the level of miR-138-5p and Scu treatment enhanced this effect, which indicated that Scu might aggravated HR injury trough upregulate miR-138-5p.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, EFhd2 may play an important role in several neurodegenerative diseases, as it is associated with tau in Alzheimer's disease and other neurological disorders (Ferrer-Acosta et al, 2013;Vega, 2016). Recently, it was found that EFhd2 is up-regulated in the cardiomyocytes during cardiac remodeling and repair (Giricz et al, 2020). Although the functions and cellular localization of EFhd1 and EFhd2 differ, the two proteins exhibit a high degree of sequence identity (65%) (Mun et al, 2021;Dutting et al, 2011;Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%